Evaluation of treatment outcome assessment using the American Board of Orthodontics Objective Grading System in subjects treated with lower incisor extraction with severe to moderate crowding - Burnett, Inna; Gandhi, Vaibhav; Alshami, Loiy; Patel, Jay; Nandakumar, Janakiraman (The Angle orthodontist, 2025)
To assess case outcomes using the American Board of Orthodontics (ABO) Objective Grading System (OGS) in patients treated with lower incisor extraction. Discrepancy indices (DI) were used to stratify patients into mild, moderate, and complex categories and overjet, overbite, and buccal occlusion were examined. Nineteen subjects were included in the study, among which 52.6% were females. The average (SD) age was 28.5 (15.1) years, and the average (SD) DI was 15.2 (8.6) with an even distribution of mild, moderate, and complex cases. The mean post-treatment OGS was 31, with 52.6% of the patients achieving passing ABO clinical scores. 31.6% achieved normal post-treatment overjet. A total of 52.6% achieved normal post-treatment overbite, and 84.2% achieved normal post-treatment buccal occlusion. An increase in overbite and overjet, and a decrease in buccal occlusion measurement, were found after lower incisor extraction treatment. The ABO-OGS scores obtained were high, indicating that they may not pass the ABO criteria established.